Masa Bimbingan Apakah Berpengaruh Terhadap Pembentukan Karakter Mahasiswa - Shofya Azzahra Muttaqin; Wilda Zahrotul Hasanah; Farid Abdul Wahid; Aditia Nugraha; Muhammad Zafharani El-Shabaz; Rama Wijaya Abdul Rozak; Ariyano Ariyano (Institut Nalanda, 2023)
Guidance Period activities which are considered ineffective, are examined to find out how good they are for students, so that they become a material for consideration and reference for evaluating these activities in subsequent years. Reviewed by giving questionnaires to several respondents with special criteria, and observed through naturalistic observation methods. It was found that the frequency of the influence of the guidance period on several aspects, namely: 1) time management, 2) comply with regulations, 3) be ethical, 4) be responsible, the average agree: 86.6% and disagree: 13.3%. Meanwhile, in the observation results, it was found that the behavior of some respondents did not match the answers to the questionnaire which was influenced by several factors, namely internal factors in the form of individuals and external factors in the form of education and the environment. It is hoped that the inhibiting factors on the effect of the Guidance Period activities found through this research can be the basis for increasing the good habits of respondents and improving these activities so that they become better.